Decomposition and iterative aggregation in hierarchical and decentralised planning structures - Jörnsten, Kurt O.; Leisten, Rainer (European journal of operational research, 1995)
The interpretation of decomposition approaches, originally developed for the solution of large-scale programming problems, as a representation of the planning process in a divisionalised enterprise has been treated intensively in literature. In contrast, iterative aggregation and disaggregation is seldom discussed with respect to organisational or planning aspects. This paper intends to interpret iterative aggregation in an organisational (divisionalised) context and tries to compare basic decomposition approaches with basic aggregation approaches focusing on the information flow between the different organisational levels. We also present several modifications of the standard aggregation approach and interpret them in an organisational context. The standard block-angular LP-model used implies that the structure of the organisational problem is reduced to a situation in which the co-ordination between the two organisational levels is simplified mainly to a communication process of exchanging information between the different levels.